EVALUASI PROGRAM KOTA SEHAT DI KECAMATAN WOLIO KOTA BAUBAU - Yunizal Nisaid; Andi Arya Maulana Wijaya; Sry Mayunita (Halu Oleo University, 2024)
This study aims to evaluate the Healthy City Program in Wolio District, Baubau City, focusing on inter-agency conditions, community participation, institutional aspects, and program impact. This research employs a qualitative descriptive approach, with in-depth interviews as the primary data collection method. The informants of this study include the Chairpersons of the Working Groups in each Kelurahan, the Coordinators of the Healthy City Forum in Wolio District, the Coordinators of the Human Resources and Resource Mobilization Section, the Coordinators of the Tatanan Development and Evaluation Section, and the program beneficiaries. The results show that the coordination between agencies in implementing the Healthy City Program in Wolio District is quite effective, although some communication barriers and task distribution issues need improvement. Community participation is relatively high, especially in cleanliness and environmental health activities, but there are still challenges in engaging all community layers actively. Institutionally, there is a clear structure, and training is provided to the Working Group members, although internal evaluation needs enhancement. The program's impact is positively perceived by the community, with improvements in environmental quality and health. However, the program's sustainability requires better inter-agency coordination and broader community participation. This study contributes to understanding the effectiveness and challenges of the Healthy City Program and provides recommendations for improving the program's implementation in the future.